136k views
0 votes
Simplify the expression (9+4i)^2

User Jammie
by
5.3k points

2 Answers

3 votes

Answer:

65+72i

Explanation:

The given expression is


(9+4i)^2

We need to find the simplified form of given expression.

Using perfect square formula, we get


(9+4i)^2=(9)^2+2(9)(4i)+(4i)^2
[\because (a+b)^2=a^2+2ab+b^2]


(9+4i)^2=81+72i+(4)^2(i)^2


(9+4i)^2=81+72i+16(-1)
[\because i^2=-1]

On further simplification we get


(9+4i)^2=81+72i-16

Combined like terms.


(9+4i)^2=(81-16)+72i


(9+4i)^2=65+72i

Therefore, the simplified form of given expression is 65+72i.

User Tennile
by
5.8k points
1 vote

(9+4i)^2

(9+4i) (9+4i)

FOIL

first = 9*9 =81

outer = 9*4i = 36i

inner = 4i*9 = 36i

last = 4i*4i = 16 i^2 (i^2 = -1) so 16 *(-1) = -16

add them together

81+ 36i + 36i-16

81-16+36i+36i

65+72i

User Zennichimaro
by
4.9k points